Ali je linearno ovrednotenje vpliva vetra na dolžino skoka smučarjev skakalcev res ustrezno? - Jošt, Bojan (Šport (Ljubljana), 2023)
The length of a ski jumper’s jump can be typically influenced by the wind. In 2010, the International Ski and Snowboard Federation (FIS) introduced a new method to evaluate the effect of wind on jump length. This method has undergone minor changes. In the last 2022/2023 season, too, there were occasional significant influences of wind on jump length. At the World Cup in Willingen on 3 February 2023, the Slovenian jumper Timi Zajc jumped 161.5 m. His jump length exceeded the size of the 147 m hill by 14.5 m and beat the current hill record of 153 m by 8.5 m. An analysis of his six jumps on this hill shows that this extreme distance can be mainly attributed to the effect of the wind and not to a fundamentally different jump by the jumper himself. In the calculation of the correction points for the length of the jump due to the effect of the wind, a hypo- thetical problem is becoming more and more apparent when using the current linear model. As suggested by some empirical and theoretical arguments, a non-linear model for the calculation of jump length correction points would be more appropriate when evaluating the effect of tangential wind. The approximate non-linear method used in this study to evaluate the effect of tangential wind proved to be a much fairer and more accurate method of estimating the corrected jump length in this practical example. It is becoming increasingly apparent that the current official FIS linear method of evaluating wind correction is no longer appropriate and that it is high time it was changed.
Keywords: dolžina skoka; smučarski skoki; šport; veter; vpliv vetra